Processed Food Innovation using Oyster Mushroom - Abdul Razzaq, Abdul Rasid; Syed A. Kadir, Syed Shikh; Che Ahmad, Che Noor Nura Adilla; Abdul Rahman, Abdul Wafi Abdul Rahman; Harun, Hairuddin; Rohiat, Mohd Akmal; Raden Ismail, Raden Mohd Farhan Helmi (Research and Innovation in Technical and Vocational Education and Training, 2021)
The purpose of this study is to develop of innovative nugget product based on an oyster mushroom. This study’s main objective is to observe the nugget’s durability from the oyster mushroom and get to know the best way to package the product to long-lasting store in the fridge. From the study and experiment conducted, experiment 1, which is steamed and dried the oyster mushroom at the first of the experiment, showed that it does not fulfill the criteria of the aroma, color, and taste of the oyster mushroom nugget. While in experiment 2, the oyster mushroom was steamed and burnt first, it showed the best result for aroma, color, and taste of the oyster mushroom nugget. Overall, project’s objective has been achieved for this research. It was discussed in all the problem statements at the beginning of the study.